Consolidated Groups of Taxpayers: Size and Impact on Economic Growth - Bannova K. A. Kristina Alekseevna; Pokrovskaya N. V. Nataljya Vladimirovna; Dyrina E. N. Evgeniya Nikolaevna; Ryzhakina T. G. Tatiana Gavrilovna; Koroleva N. V. Nataljya Valentinovna (2016, 2016)
Title screen